Research on the Value Creation, Ethical Challenges and Response Strategies of Robots in Government Administrative Performance Management - Zhong, ChengZhang (Innovative Applications of AI, 2025)
Although the application of robots in government administrative performance management can significantly improve efficiency and accuracy, the ethical issues it raises, such as data privacy, algorithmic bias, and responsibility attribution, are becoming increasingly prominent. Most current studies focus on technical effectiveness, but ignore the systematic governance of ethical risks. This article analyzes the impact of robot automated decision-making on administrative fairness and the legal dilemma caused by the ambiguity of the subject of responsibility, revealing the loopholes and defects of the existing governance framework. With regard to these issues, the study advocates the establishment of an ethical governance structure with multi-stakeholder collaboration, the optimization of the algorithm audit mechanism, and the improvement of the responsibility traceability system. In order to balance technological innovation and ethical compliance , the study provides a theoretical basis and practical solutions for the standardized development of intelligent administration.